MATRIX TYPE TRANSDERMAL THERAPEUTIC SYSTEM CONTAINING CAPTOPRIL: FORMULATION OPTIMIZATION, IN VITRO AND EX VIVO CHARACTERIZATION - (:unkn) unknown (POLSKIE TOWARZYSTWO FARMACEUTYCZNE, 2013)
Transdermal therapeutic systems (TTS) containing captopril were developed by using synthetic and pH independent polymers, Eudragit RL 100 and RS 100. The formulations were characterized in terms of their appearance, thickness, captopril content, in vitro release rate and diffusion profiles. In vitro release studies demonstrated controlled release for each formulation developed. In vitro and ex vivo diffusion rate studies were performed through various synthetic membranes with different thickness, pore size and type (hydrophilic and hydrophobic) and through human skin by using Franz diffusion cells. Type of membrane and composition of the formulation affected the diffusion profiles of captopril from the transdermal therapeutic systems. Transdermal therapeutic systems containing captopril were successfully prepared and especially two of the formulations (F15 and F16) are considered to be suitable to administer captopril via skin.
Keywords: captopril; transdermal delivery; patch; synthetic membranes; human skin; EXCISED RABBIT SKIN; PERCUTANEOUS-ABSORPTION; ENHANCERS